Food Quantity Discrimination in Angelfish (Pterophyllum scalare): The Role of Number, Density, Size and Area Occupied by the Food Items - Gómez-Laplaza, Luis M.; Gerlai, Robert (Frontiers in Behavioral Neuroscience, 2020)
Quantity discrimination, the ability to identify, process and respond to differences in number, has been shown in a variety of animal species, and may have fitness value. In fish, the ability to distinguish between numerically different shoals has been well studied. However, little work has been devoted to the investigation of such ability in a foraging context. Nevertheless, angelfish (Pterophyllum scalare) have been previously shown to be able to discriminate numerically different sets of food items, with variables such as size and density of the food items playing important roles in making the choice. Here, we examine the possible role of other non-numerical variables. Using a spontaneous binary choice task, we contrasted sets of food items differing in specific controlled ways: 1, different numerical size but equal inter-item distance; 2, different numerical size and different inter-item distance; 3 identical total contour length and area occupied but different individual food size and inter-food distance between the contrasted food sets. In Experiment 1, angelfish were found to prefer the sets with the large number of food items. In Experiment 2, they preferred the numerically smaller sets with clustered items to the numerically larger sets with scattered items, but only when the sets were in the large number range (10 vs. 5 food items). Finally, in Experiment 3 fish preferred numerically smaller sets with large-sized and scattered food items in the large number range sets. We conclude that food item number, density and size may not be considered individually by angelfish, but instead the fish respond to all these factors attempting to maximize energy gained from eating the food while minimizing energy expenditure collecting and/or protecting the food.